Nanoscale Communications Based on Fluorescence Resonance Energy Transfer (FRET) - Kuscu, Murat; Akan, Ozgur B. (Modeling, Methodologies and Tools for Molecular and Nano-scale Communications, 2017)
Nanoscale communication is a novel and quite interdisciplinary research area which aims to design and develop communication networks among nano-size machines to extend their limited capabilities for groundbreaking biomedical, industrial and environmental applications [1].